Zikir Mahasantri Ma’had Al-Jami’ah UIN Raden Fatah Palembang Ditinjau dari Perspektif Ilmu Tarekat (The Zikr of the Students of Ma'had Al-Jami'ah UIN Raden Fatah Palembang Viewed From the Perspective of Tarekat Science) - Nyayu Siti Zahrah (Institut Agama Islam Negeri (IAIN) Manado, 2021)
ABSTRACT This study examines the zikr of the students of Ma'had al-Jami'ah UIN Raden Fatah Palembang from the perspective of tarekat science. This research was motivated by the existence of a zikr ritual performed by students at Ma'had al-Jami'ah UIN Raden Fatah Palembang which, through observation, had similarities with the teachings of Sufism and several tarekat schools, both in terms of adab, reading, movement, tone and intonation. Therefore; the author analyzed the zikr of the students of Ma'had al-Jami'ah UIN Raden Fatah in terms of the tarekat science perspective. In this study, the author uses a type of qualitative research with phenomenological analysis which means observing the phenomena that occur during the research. The results of this study are that the zikr performed by Ma'had al-Jami'ah students at UIN Raden Fatah Palembang has the same purpose as the zikr goals in Sufism teachings, namely to get closer to Allah, while in terms of reading, it has similarities with the recitation of the zikr in the Naqsabandiyah congregation. In terms of the adab and the movement, they are more of the ones of the zikr in the teachings of Sheikh Abdus Samad al-Palimbani. However, the tone and intonation of the zikr performed by the students partly have similarities with the tone and intonation of the zikr on the teachings of the Sammaniyah order. This is because the imam of the zikr, Mr. Munir, is a follower of two tarekat schools, namely the Naqsabandiyah and the Sammaniyah congregations.Keywords:zikr; mysticism; tarekat.ABSTRAKPenelitian ini mengkaji tentang zikir mahasantri Ma’had al-Jami’ah UIN Raden Fatah Palembang yang ditinjau dari perspektif ilmu tarekat. Penelitian ini dilatarbelakangi oleh adanya ritual zikir yang dilaksanakan oleh mahasantri di Ma’had al-Jami’ah UIN Raden Fatah Palembang yang ketika diamati zikir ini memiliki kesamaan dengan ajaran tasawuf dan beberapa tarekat, baik dari segi adab, bacaan, gerakan, nada dan intonasi. Maka dari itu, penulis ingin menganalisis zikir mahasantri Ma’had al-Jami’ah UIN Raden Fatah ditinjau dari perspektif ilmu tarekat. Dalam penelitian ini, penulis menggunakan jenis penelitian kualitatif dengan analisis fenomenologi yang berarti mengamati fenomena-fenomena yang terjadi pada saat penelitian berlangsung. Adapun hasil penelitian ini adalah bahwa zikir yang dilaksanakan oleh mahasantri Ma’had al-Jami’ah UIN Raden Fatah Palembang memiliki tujuan yang sama dengan tujuan zikir pada ajaran tasawuf yaitu untuk mendekatkan diri kepada Allah, sedangkan dari sisi bacaan, zikir yang dilakukan mahasantri Ma’had al-Jami’ah sebagian besar memiliki kesamaan dengan bacaan zikir pada tarekat Naqsabandiyah, tetapi dari sisi adab zikirnya lebih kepada adab zikir ajaran Syekh Abdus Samad al-Palimbani, namun nada dan intonasi zikir yang terdapat dalam zikir ini sebagian memiliki kesamaan dengan nada dan intonasi zikir pada ajaran tarekat Sammaniyah. Sedangkan gerakan zikirnya mengikuti gerakan zikir dari ajaran Syekh Abdus Samad al-Palimbani. Hal ini dikarenakan imam zikir tersebut yaitu Bapak Munir merupakan pengikut dua aliran tarekat yaitu tarekat Naqsabandiyah dan tarekat Sammaniyah.Kata kunci: zikir; tasawuf; tarekat